Pengembangan model buku saku penataan budaya sekolah berbasis profil pelajar pancasila - Listari, Icha Dwi; Sukriono, Didik; Suhartono, Edy (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
Bullying, physical violence, unfriendliness, and a lack of empathy or sympathy have contributed to a moral crisis in this country, especially among children in school environments. The Pancasila Student Profile is the abilities, character, and competencies that Indonesian students must possess in the 21st century to strengthen their character with six elements that must be applied in daily life.  The purpose of this article is to produce a book on school culture development based on the Pancasila Student Profile. Based on the author's background and objectives, the research method used in this study is the ADDIE development model, which consists of five phases: analysis, design, development, implementation, and evaluation. The research tools used include media, language, and expert student assessment sheets. The results of the pocket book development research on media experts obtained a percentage of 83% with a category of sufficiently valid. Language experts obtained a percentage of 82.69%, which was deemed sufficiently valid. The results of the small-group trial obtained a percentage of 76%, while the results of the large-group trial obtained a percentage of 92% with a category of highly valid and applicable to 10th-grade students at Muhammadiyah 10 High School in Surabaya.